Isolated Intraspinal Extradural Tubercular Lesion without Osseous Involvement - Sharad Pandey; Deepa Pandey; Kulwant Singh; Vivek Sharma; Amrita Ghosh (Indian Journal of Neurosurgery)
Tuberculosis (TB) continues to be a major public health problem in developing countries. Approximately 10% of patients with extrapulmonary TB have skeletal involvement. The spine is the most commonly affected skeletal site. The neurologic manifestations of spinal TB are most often secondary to bone involvement but can also be due to neural and perineural tissues involvement. TB may involve any level from the cervical to lumbosacral region. Extradural tubercular granuloma without vertebral involvement is uncommon. The authors reported an uncommon case of isolated intraspinal extradural TB lesion without osseous involvement of the thoracic spine in an adult man. Surgical intervention along with chemotherapy is one of the preferred treatments for intraspinal extradural tubercular lesion.